Performance Based Bureaucracy pada Aparatur Sipil Negara di Inspektorat Kabupaten Enrekang - Hajar, Siti; Abdi, Abdi; Kasmad, Rulinawaty (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2020)
This study aimed to determine the Performance Based Bureaucracy of the Civil Servants. How Performance Based Bureaucracy in the Civil Servants measured performance through four strategies, aimed at improving the quality of existing human resources at the Enrekang Regency Inspectorate. This study used   Phenomenological. This type was qualitative research, data sources consisted of primary data and secondary. The results of this study showed that performance-based bureucracy in producing four performance-based bureucracy strategies that had  a namely passive strategy, political strategy, perverse straregi, purposeful strategy were already running well as evidenced by the criteria for success indicators of knowledge, technical skills and behavioral attitudes as well as accuracy or performance targets although there was little that needs to be addressed so that Civil Servants had better quality performance.